2018
DOI: 10.1002/jcph.1143
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic/Pharmacodynamic Analysis of Isavuconazole Against Aspergillus spp. and Candida spp. in Healthy Subjects and Patients With Hepatic or Renal Impairment by Monte Carlo Simulation

Abstract: The aim of this pharmacokinetic/pharmacodynamic (PK/PD) study is to evaluate the efficacy of various isavuconazole dosing regimens for healthy individuals and patients with hepatic or renal impairment against Aspergillus spp. and Candida spp. Monte Carlo simulations were conducted using pharmacokinetic (PK) parameters and pharmacodynamics (PD) data to determine the probabilities of target attainment and cumulative fractions of response in terms of area under the concentration curve/minimum inhibition concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, platinum isavuconazole had a max CFR value of 80.68% under different dosing regimens [15]. Isavuconazole had a max CFR value of 62.70% under different dosing regimens [16]. In this study, Monte Carlo simulation analysis showed that rezafungin in healthy people could obtain good results when the dosage is 50 mg, which provides a basis for subsequent clinical research and application.…”
Section: Discussionmentioning
confidence: 66%
“…For example, platinum isavuconazole had a max CFR value of 80.68% under different dosing regimens [15]. Isavuconazole had a max CFR value of 62.70% under different dosing regimens [16]. In this study, Monte Carlo simulation analysis showed that rezafungin in healthy people could obtain good results when the dosage is 50 mg, which provides a basis for subsequent clinical research and application.…”
Section: Discussionmentioning
confidence: 66%
“…In a recently published PK/PD study, Zheng et al examined the efficacy of various isavuconazole dosing regimens for healthy individuals and patients with renal and hepatic impairment, namely Child-Pugh Class A or B cirrhosis, against Aspergillus spp. and other fungi [134]. The Monte Carlo simulation was used in each scenario to calculate target attainment and cumulative fractions of response probabilities.…”
Section: Antifungal Agentsmentioning
confidence: 99%
“…The clinically recommended dose of 200 mg isavuconazole per day was effective for all individuals against A. fumigatus , A. flavus , A. nidulans , A. terreus , and A. versicolor . [134].…”
Section: Antifungal Agentsmentioning
confidence: 99%